Optimización de la unión disímil ASTM A516/316L soldada con arco pulsado con el electrodo ER-2209 - Panadés Barrueta, Leonardo (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
In this research work, the optimal parameters for the dissimilar ASTM A516/316L weld using pulsed arc welding with the ER-2209 electrode were established to prevent or reduce metallurgical interactions that may negatively affect the performance of this dissimilar joint. To achieve this, the dissimilar welding of these steels was initially carried out in DC-Pulsed synergic mode for welding carbon steels using the OTC Daihen WelBee DP-400 welding power source. A macrostructural and microstructural characterization of the joint was then performed to analyze the metallurgical interactions in the welded joint. Subsequently, the dissimilar joint was welded using a pulsed arc process for optimization through an experimental design based on Taguchi’s methodology, employing an L9 orthogonal array and analysis of variance (ANOVA). To assess the factors analyzed in this methodology, a macrostructural and microstructural characterization of the welded joint was conducted. Based on the reference welds, the welding parameters for the orthogonal array were determined as follows: peak current (Ip), base current (Ib), and peak time (tp). The optimal conditions were established using Taguchi’s "smaller-is-better" criterion. It was observed that the use of the optimal parameters Ip, Ib, and tp influenced the size of the heat-affected zone (HAZ) in the ASTM A516 Gr. 70 base metal. The contribution percentages of each factor were estimated through variance analysis, determining that the greatest contribution to the HAZ extension came from Ip (61.26 %), followed by Ib (11.86 %) and tp (9.71 %).

En este trabajo de investigación se establecieron los parámetros óptimos de la unión disímil ASTM A516/316L soldada con arco pulsado con el electrodo ER-2209 con el fin de evitar o disminuir las interacciones metalúrgicas que generan inconvenientes para el rendimiento de esta unión disímil. Para ello se partió de la realización de la soldadura disímil de estos aceros en modo sinérgico DCPulsado para soldar aceros al carbono utilizando la fuente de soldadura OTC Daihen modelo WelBee DP-400 y se realizó la caracterización macro y microestructural de la junta para tener referencia de las interacciones metalúrgicas en la junta soldada. Posteriormente, se realizó la soldadura de la junta disímil con arco pulsado para su optimización mediante un diseño de experimentos de acuerdo con la metodología Taguchi con un arreglo ortogonal L9 y análisis de varianza (ANOVA por sus siglas en inglés). Para valorar los aspectos a analizar de la metodología se realizó una caracterización macro y microestructural de la junta soldada. A partir de las soldaduras de referencia se establecieron los parámetros de soldadura para el arreglo ortogonal los cuales fueron; corriente pico (Ip), corriente de fondo (Ib) y tiempo en los picos (tp). Las condiciones óptimas fueron establecidas a través de la metodología Taguchi bajo el criterio ``menor es mejor´´. Se observó que el uso de los parámetros óptimos Ip, Ib y tp afectan en el tamaño de la ZAT del metal base ASTM A516 Gr. 70. Se estimaron los porcentajes de contribución de cada uno de los factores por análisis de varianza. Se determinó que para la extensión de la ZAT la mayor contribución fue para Ip con 61.26 % y para Ib y tp fueron 11.86 % y 9.71 %, respectivamente.
Instituto de Investigación en Metalurgia y Materiales. Maestría en Metalurgia y Ciencias de los Materiales
Keywords: info:eu-repo/classification/cti/7; IIMM-M-2025-0291; Taguchi; Arreglo ortogonal; Soldadura disímil; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19251